MAIO : Chromatic Gestures
Se compilan proyectos e investigaciones del estudio MAIO. Contiene: 40 Social Housing Units Building in Sant Feliu de Llobregat (Spain). Territorio de Gigantes, Aguascalientes (Mexico). Refurbishment of a Studio-Garden House in Barcelona (Spain). Refurbishment of a House in Barcelona (Spain). Sport Center in Barcelona (Spain, MAIO + Jorge Vidal). House in Empordà (Spain). Housing in Bilbao (Spain). Diffuse House.
Keywords: MAIO; CHARNECO, MARÍA; LÉRIDA, ALFREDO; LÓPEZ, GUILLERMO; PUIGJANER, ANNA; VIDAL, JORGE; ESPAÑA; LLOBREGAT; MEXICO; AGUASCALIENTES; BARCELONA; BILBAO; PROYECTOS; CONCURSOS; INVESTIGACIONES; CONJUNTOS HABITACIONALES; EDIFICIOS DE VIVIENDAS; JARDINES; RENOVACIÓN; RENOVACION ARQUITECTONICA; VIVIENDAS UNIFAMILIARES; CENTROS DEPORTIVOS; TIPOLOGIAS